Synthesis and lubricating properties of neopentyl glycol oligoesters based on rapeseed oil. Issue 5 (10th August 2015) - Liao, Dezhong; He, Jieyu; Mao, Lixin; Xu, Yixue
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The aim of this work is to synthesize neopentyl glycol oligoesters based on adipic acid and rapeseed oil (NOAR) which may be used as the renewable and environmentally acceptable base fluids to replace mineral oils in the future. Design/methodology/approach – Oligomeric intermediates were synthesized in the first esterification of neopentyl glycol with adipic acid and characterized by Gas Chromatography-Mass Spectrometer (GC-MS) to calculate the average oligomerisation degree. NOAR were synthesized in the second esterification of oligomeric intermediates with rapeseed oil fatty acid. The effects of average oligomerisation degree on the viscosity, viscosity index, pour point, oxidative stability and biodegradability of NOAR were investigated; the tribological properties and thermal stability of NOAR were evaluated by four-ball tribometer and TGA, respectively. Findings – Results show that with the increase of average oligomerisation degree from 2.10 to 4.34, the viscosity of NOAR increased from 101.1 to 182.0 (mm2/s) at 40°C and 18.3 to 30.1 (mm2/s) at 100°, respectively, and their oxidation stability can be improved as well. The yields of NOAR were 83.3-89.4 per cent, and the evaluated properties were as follows: viscosity index of over 200, pour point of below −43°C, biodegradation rate of more than 96 per cent, maximum non-seizure load (PB value) of 784 N, wear scar diameters of 0.40 mm and thermal decomposition temperature of higher than 300°C. Originality/value – This work provides a method to synthesize rapeseed oil-based oligoesters which can serve as the renewable and environmentally acceptable base fluids with tunable viscosity by controlling the oligomerisation degree of esterification.